Effects of gold and green kiwifruit juices on the physicochemical properties and tenderness of pork loin and antioxidant activity during incubation (24 h) in a pork model system - Haeun Kim; Koo Bok Chin (Animal Bioscience, 2024)
Objective Although pork loins is not a tough meat, they need to develop meat products with a soft texture for the elderly. This study focused on the physicochemical properties and tenderness characteristics of pork loin injected with green kiwifruit juice (GRJ) and gold kiwifruit juice (GOJ) during various incubation times. In addition, the antioxidant activities of hydrolysate derived from the hydrolysis of pork loin by kiwifruit juice protease were evaluated. Methods The pork loin was injected with 10% and 20% GRJ and GOJ, under various incubation times (0, 4, 8, and 24 h). Then, the physicochemical properties and tenderness of pork loins were measured. 2,2- diphenyl-1-picrylhydrazyl radical scavenging activity and reducing power were conducted to determine hydrolysate’s antioxidant activities derived from pork loin’s hydrolysis by kiwifruit juice protease. Results GRJ had greater tenderizing ability than GOJ, even at the 10% addition. When kiwifruit juice was injected into pork loin, the tenderness increased with increasing incubation time. This was confirmed by the decrease in intensity of the myosin heavy chain (MHC) band in sodium dodecyl sulfate–polyacrylamide gel electrophoresis. In particular, the MHC band decreased at 8 h for both 10% GRJ and 20% GOJ and at 4 h for 20% GRJ alone. The highest myofibril fragmentation index and peptide solubility were observed in pork loin treated with 20% GRJ compared to the other treatments during incubation. The 10% GRJ and 20% GOJ treatments showed similar levels of antioxidant activity of the protein hydrolysates in pork loin, and 20% GRJ showed the highest activity among the treatments. Conclusion Kiwifruit juice had protease activity, and GRJ was more useful for tenderizing meat products than GOJ. Thus, GRJ at 10% could be a potential agent to tenderize and enrich the natural antioxidant activity through the proteolysis of pork loin.